Effect of religious fatalism and concern about new variants on the acceptance of COVID-19 vaccines - Tito Betancur, Madona (2023)
Introduction: To protect public health, it is important that the population be vaccinated against COVID-19; however, certain factors can affect vaccine acceptance. Objective: The objective of this study was to determine whether religious fatalism and concern about new variants have a significant effect on the acceptance of COVID-19 vaccines. Methodology: An explanatory study was conducted with 403 adults of legal age captured through non-probabilistic convenience sampling in vaccination centers in the 13 health networks of the Regional Health Directorate of Puno, Peru. Data were collected through a brief scale of religious fatalism, a scale of acceptance of vaccines against COVID-19 and a scale of concern about a new variant of COVID-19. Results: The proposed model obtained an adequate fit. There was a negative effect of religious fatalism on vaccine acceptance, a positive effect of fatalism on vaccine rejection, a positive effect of concern about new variants on the acceptance of vaccines, and a positive effect of concern about new variants on vaccine rejection. Conclusion: These findings provide evidence for the usefulness of considering both religious fatalism and concern about new variants affect the intention to receive the COVID-19 vaccine in adults in southern Peru.